2005
DOI: 10.1159/000091441
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy for Colorectal Cancer

Abstract: Colorectal cancer is the most commonly diagnosed cancer in the EU. Various randomised studies have shown a survival benefit with chemotherapy in the adjuvant setting. Adjuvant chemotherapy with 5-fluorouracil/folinic acid (5FU/FA) for 6 months after curatively resected node-positive colon cancer has become the standard practice. However, controversy still exists regarding the optimal regimen and whether to treat node-negative patients. The latest QUASAR trial results seem to strengthen the argument in favour o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 114 publications
0
38
0
Order By: Relevance
“…The development and approval of novel therapies, including the monoclonal antibodies bevacizumab (anti-vascular endothelial growth factor; Avastin) and cetuximab (anti-EGFR), have increased median survival of patients with metastatic colon cancer to f24 months (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…The development and approval of novel therapies, including the monoclonal antibodies bevacizumab (anti-vascular endothelial growth factor; Avastin) and cetuximab (anti-EGFR), have increased median survival of patients with metastatic colon cancer to f24 months (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Protracted infusional regimes were developed to maximise 5FU dose intensity. They have been found to be as effective as the bolus regimens and less toxic, with less impact on quality of life (Andre et al, 2003;Saini et al, 2003;Goyle and Maraveyas, 2005 (Goyle and Maraveyas, 2005). The other major factor likely to result in failure to complete chemotherapy is toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…As important group of antineoplastic drugs, 5-fluoropyrimidines and pemetrexed could target on TS, and are widely used in the treatment of gastrointestinal tumors, breast tumors, and epithelial tumors of the upper aero digestive tract (Grem, 1988;Goyle et al, 2006). Previous studies performed on several cancers have demonstrated that the TS expression level predicted the response to 5-FU or pemetrexed chemotherapy (Foekens et al, 2001).…”
Section: Discussionmentioning
confidence: 99%